Organosoluble, esterified starch as quasi-solid biopolymer electrolyte in dye-sensitized solar cell - Selvanathan V.; Ruslan M.H.; Alkahtani A.A.N.; Amin N.; Sopian K.; Muhammad G.; Akhtaruzzaman M. (Elsevier Editora Ltda, 2023)
Biomolecules; Biopolymers; Cost effectiveness; Crystallinity; Dimethylformamide; Dye-sensitized solar cells; Efficiency; Esters; Fourier transform infrared spectroscopy; Hydrophilicity; Ionic conductivity; Lithium compounds; Polyelectrolytes; Reinforced plastics; Biopolymer electrolyte; Dye- sensitized solar cells; Electrochemists; Esterified starch; Organosoluble; Phthaloylation; Property; Quasi-solid electrolyte; Quasi-solid state; Solid state polymer electrolyte; Solid electrolytes